Prevalence of High-Risk Human Papillomavirus (HPV) among Negative Visual Inspection of Acetic Acid (VIA) - Utami, Tofan W (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: Persistence of high-risk HPV infection is known to be the major cause of cervical cancer. It is important to differentiate the genotype of HPV infection, whether it is high, intermediate or low risk. The aim of this study was to assess the prevalence of high-risk HPV types among Indonesian women with negative VIA. Method: We analyzed cervical swabs from 1,214 patients with negative VIA. By using INNO-Lipa HPV DNA test, we detected the HPV DNA and its genotype. Result: From the 1,214 women with negative VIA, 48 (3.95%) samples were confirmed to have positive HPV DNA by using PCR and electrophoresis. However, hybridization test were not able to detect HPV genotypes in 9 samples. These 9 samples were tested again with PCR and electrophoresis and resulted in negative HPV DNA. Among the remaining 39 samples (3.21%), we detected 19 types of HPV, consisting of 13 types of high-risk HPV, 5 types of low-risk HPV, and 1 type of unknown HPV (type X). Conclusion: Among patients with negative VIA, 3.21% was found to be positive for HPV DNA. From this percentage, the prevalence of high-risk HPV is higher than the low-risk and unknown HPV. Therefore we cannot ignore results of negative VIA, particularly in highrisk group, because there is a slight possibility that presence of HPV can be identified, especially the high risk ones which have a tendency to be persistent. We support the importance of HPV DNA test as cervical cancer screening method. [Indones J Obstet Gynecol 2014; 3: 153-156] Keywords: cervical cancer, high-risk HPV, negative VIA